Avaliação das propriedades de superfície na eletroerosão no aço AISI P20 e na liga de alumínio 7075-T6 - Rossetto, Artur da Silva (2022)
The present study proposes the evaluation of penetration EDM machining on productivity and surface integrity of AISI P20 steel and 7075-T6 aluminum alloy. This aluminum alloy stands out as a replacement for AISI P20 steel in the manufacture of injection molds for thermoplastics. For the study, specimens were machined in roughing, semi-finishing and finishing regimes. Analysis of variance (ANOVA) was used to analyze the effects of the factors and verify significant differences in surface roughness (Ra and Rz) and material removal rate (MRR). For the analysis of surface integrity, microscopy evaluations and microhardness tests were performed. The MRR and the roughness showed that the semi- finishing regime presented the best results, where it was obtained in the aluminum alloy, roughness close to that of steel with a marked increase in productivity. The extension of the thermally affected zone (TAZ), noticeable by the reduction of microhardness, and the thickness of the reformulated layer, increased with the severity of the regimes in the steel. In the aluminum alloy, the increase in the thickness of the reformulated layer is not visible with the change of regimes, and the TAZ of the three samples presented similar microhardness values, slightly lower than that of the base metal. Microscopy revealed different topographies between the materials, with superficial defects on a micrometric scale. Unlike steel, it was verified the absence of microcracks in the reformulated layer of aluminum alloy, this is an excellent finding for the useful life of the mold. Compared to AISI P20 steel, the AL7075-T6 alloy has shown promising results in terms of the use of electro-erosion machining in the manufacture of molds for thermoplastic injection.